Common Presenting Symptoms In Children Seeking First Aid Service In A Urban School - Sharma, Lucky; Sharma, D (Journal of General Practice and Emergency Medicine of Nepal, 2011)
Introduction: School is an important place next to home where a child learns to be healthy. Children may seek first aid services in a school for various reasons, so there should be a proper health system in school where these problems are addressed.Method: This is a descriptive observational study done at N. K Sing Memorial English Preparatory School. The study duration was 12 month from Baisakh 2067 to Chaitra 2067. Data were collected in school hours from 9 am to 4 pm everyday except on government holidays and vacation. List of presenting complaints from all systems were given and nursing staff were appointed in the dispensary who were trained to collect data. Number of visits in dispensary was recorded rather than the number of patients.Result: Total 4082 visits were taken for the study; the average visits per day were 19.8 with SD ± 5.3. Out of 4082 visits, 44.1% of visits were by males and 55.9% of visits were by females. The mean age was 9.7 years with SD ± 2.2 years, 4.9% of visits were from age group less than 5 years, 52.3% of visits were from age group 5 to 10 years and 42.8% of visits were from the age group more than 10 years. The top five symptoms bringing students to dispensary were trauma (15.6%), Diarrhea and vomiting (14.7%), cough and Cold (11.3%) and Headache (10.7%). Visits were relatively more common in summer (66.1%).Conclusion: There are various health necessities of school going children which need immediate first aid support. The strategy should be implemented to reinforce this need in school health program.